Service Quality Analysis to Increase Customer Satisfaction in National Flight Company - Jessica; Kenneth Kaleb; Muhammad Fadhil Raksiwi; Raymond Tjiwidjaja (Yayasan Gema Bina Nusantara, 2024)
This research aims to analyze service quality to increase customer satisfaction. In this research, the population used is respondents who have chosen and used an airline. The data collection method used is a quantitative method using Google Form as a survey medium. The sampling technique used is non-probability sampling with a purposive sampling type. A total of 100 respondents were collected for this survey. According to the importance performance analysis that has been carried out, it can be seen that in quadrant 1, there are two points that are the main problems with the service, namely departure comfort and baggage handling. This occurs because there is a large gap between the high level of importance of these variables and their performance, which is quite low. This can be seen from the many complaints that occur regarding departure times. Then, if you look at quadrant 2, there are the variables of friendliness of the crew, ability and level of assistance provided by the crew, care and tidiness of crew members, cleanliness of the aircraft cabin, cleanliness of the aircraft toilet, on-board catering, comfort of the seats. According to consumers, these variables are important, but the company's performance is also good in these variables. Then in quadrant 3, there is a variable regarding the availability of magazines and newspapers on the plane, which according to consumers is not important, but according to the performance, it is also poor in this variable. And finally, in quadrant 4, there are no aspects or service indicators from airlines that have excessive performance compared to their importance.